Tambahan bracket pajak penghasilan orang pribadi dalam mengatasi ketimpangan ekonomi di Indonesia - Nurjanah, Risandy Meda; Rahmiati, Alfa (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
The self-assessment system implemented within Indonesia's taxation framework since 1983 has posed compliance challenges that potentially hinder the primary function of taxes as a source of state revenue. Such trade-offs are an inevitable aspect of tax policy implementation. Over the past decades, various tax reforms have been introduced to address low tax ratios, caused by uneven tax burdens among taxpayers, and to reduce economic inequality. As one of the primary functions of taxation, income redistribution is expected to play a significant role in mitigating inequality. This study aims to analyze the impact of a new policy introducing additional brackets for Personal Income Tax on reducing economic inequality in Indonesia. Using a qualitative approach, data were collected through semi-structured interviews with two informants and further elaborated with relevant literature and statistical data. The findings reveal that the policy of adding Personal Income Tax brackets has the potential to reduce economic inequality, provided it is supported by effective taxpayer compliance, tax authority oversight, and income redistribution policies.